2014
DOI: 10.1177/0013164414554931
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Differential Effects Using Regression Interactions and Regression Mixture Models

Abstract: Research increasingly emphasizes understanding differential effects. This paper focuses on understanding regression mixture models, a relatively new statistical methods for assessing differential effects by comparing results to using an interactive term in linear regression. The research questions which each model answers, their formulation, and their assumptions are compared using Monte Carlo simulations and real data analysis. The capabilities of regression mixture models are described and specific issues to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 71 publications
1
40
0
Order By: Relevance
“…Through regression mixture models, differential effects can be found in an empirical manner; however, Van Horn et al (2009, 2015) warn that this approach is largely data driven. Therefore, it is critical that the results of studies are replicated in other samples to explore whether different samples yield different results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through regression mixture models, differential effects can be found in an empirical manner; however, Van Horn et al (2009, 2015) warn that this approach is largely data driven. Therefore, it is critical that the results of studies are replicated in other samples to explore whether different samples yield different results.…”
Section: Discussionmentioning
confidence: 99%
“…These values can range from 0 to 1, with higher scores representing greater classification accuracy. It is important to note, however, that Van Horn et al (2015) argue that entropy should not be considered a class enumeration criterion when evaluating regression mixtures.…”
Section: Methodsmentioning
confidence: 99%
“…We also hypothesized that the benefit of having multiple outcomes would be greater when the measurement error variance was larger, primarily due to jointly modeling these repeated measures outcomes. The reason for this was that the regression mixture model with a single outcome relies strongly on assumptions about the conditional distribution of that outcome for parameter estimation (Van Horn et al, 2015); with multiple outcomes, estimation is informed by the joint distribution of all outcomes, which contains more information than does the univariate distribution.…”
Section: Study Aimsmentioning
confidence: 99%
“…We anticipated that the regression mixture models would perform poorly when the Class 1 effect size was medium, given the reduced class separation from Class 2 (i.e., 0.40 vs. 0.70). We used the current setting to generate the two latent classes because we believe that if regression mixtures are to be useful for finding individual differences, they should be able to detect a difference of at least this size (Kim, Vermunt, Bakk, Jaki, & Van Horn, 2016;Van Horn et al, 2015). Although the entropy is regarded as a model fit index to show the accuracy of class assignment in general finite mixture models, it is not necessarily indicative of goodness of fit in regression mixture models.…”
Section: Data Generationmentioning
confidence: 99%
“…Kang, Janes and Huang (2014) relied on a novel boosting algorithm to choose an optimal treatment. Besides interaction models, methods based on mixture models have been proposed in Shen and He (2015) and Van Horn et al (2015). They showed that regression mixture models can be effective in evaluating differential treatment effects.…”
Section: Introductionmentioning
confidence: 99%